Child Abuse in Nigerian Polity: A Content Analysis on Two Major Newspapers - Joshua Kayode Okunade; Martha A. Odutola; Timothy Ekeledirichukwu Onyejelem (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
This study employed a content analysis on child abuse in Nigerian polity regarding two major newspapers in Nigeria, The Nation and The Guardian newspapers from January to December, 2022. Specifically, the study sought to find out the frequency of the coverage of child abuse in Nigeria newspapers, determine what category of story has the highest report in the newspapers, ascertain which newspaper shows a higher commitment to the coverage of child abuse, examine the level of prominence given to child abuse by Nigerian newspapers, and assess the direction, tone, and slant used in the reports by Nigerian newspapers. Adoption of systematic random sampling, which was used to select the sample size of the study, and purposive sampling, which was used to select two major newspapers to enable adequate knowledge of all issues in the selected newspapers for the study, were used as the sampling techniques in the process of selecting the issues for the newspapers that were analysed. The occurrences were analysed using descriptive statistics. Descriptive statistics include frequency counts and percentages with the use of SPSS version 23. The study adopted the Agenda Setting Theory. The findings showed that child abuse stories were under-reported. Only 55 issues out of 146 issues that were analysed have reports on child abuse, this means only 38% of news stories for the year 2022 from January to December 2022 had reports on child abuse while 62% had none. From this study, it was discovered that newspapers do not commit to reporting stories on child abuse. The study, therefore, recommended that efforts should be made by newspaper houses to ensure all child abuse stories are reported with in-depth analysis and are positioned on the front page of every newspaper. More so, the selected newspapers should put more attention on the fight against child abuse, because so many Nigerians are waiting to be educated and informed by the press.